Population Growth: A Comparison of Evolutionary Views - William A. Jackson (International Journal of Social Economics, 1995)
Economists are divided about population growth: the pessimism of neo-Malthusians contrasts strongly with the optimism of cornucopians. Despite their differences, both schools of thought reject economic orthodoxy and prefer evolutionary forms of theory. Their interpretations of evolution are different: the neo-Malthusians appeal to the entropy law, whereas the cornucopians emphasise human creativity expressed through markets. This paper argues that both schools are right to adopt an evolutionary outlook, but that they are too restrictive in their conception of evolution. A more complete evolutionary view, which allows properly for social institutions, could give a more balanced account of population growth.
Keywords: B52; B53; J10; J11; Q56; Q57; 330; population growth; neo-Malthusians; cornucopians; economic evolution; markets; institutions